Knowledge management in the construction industry: current state of knowledge and future research - Yepes, Víctor; López, Salvador (Journal of Civil Engineering and Management, 2021)
Knowledge management in the construction industry has become an element of transition between traditional processes and the current needs demanded by technological change. This research reviews the updated scientific contributions of knowledge management in construction, as well as its influence. The results come from a bibliometric study, elaborating a quantitative and qualitative analysis of the current state. The research method was divided into the following stages: preliminary approach to the bibliography, establishment of search strategies, selection and classification of articles, quantitative analysis and discussion of relevant articles. Three main factors were identified: use and exploitation of knowledge, knowledge transfer, and information technologies; five complementary facets were also identified: culture, innovation, quality, knowledge generation and human factors. The results reaffirm the importance of the use and exploitation of knowledge, in addition to increasing attention to the transfer and technology of information. However, the generation of knowledge has declined because the sector still does not report the results of applying knowledge, and this underlines the need for the future study of strategies to transform tacit knowledge into explicit knowledge.